Lysophospholipid (LPA) receptors in GtoPdb v.2021.3. (2021) - Blaho, Victoria; Chun, Jerold; Jones, Danielle; Jonnalagadda, Deepa; Kihara, Yasuyuki; Ngo, Tony; Ray, Manisha; Tan, Valerie P.
No abstract available